2001
DOI: 10.1302/0301-620x.83b1.11115
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic medial meniscectomy on stable knees

Abstract: We reviewed 74 partial medial meniscectomies in 57 patients with stable knees, to assess the long-term functional and radiological outcome. The International Knee Documentation Committee score and the residual laxity were assessed in both knees. At the time of surgery the mean age of the patients was 36 +/- 11 years and the mean follow-up was 12 +/- 1 years. All had a limited medial meniscectomy. The anterior cruciate ligament was intact in all cases. The meniscal tear was vertical in 95% and complex in 5%. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 29 publications
1
14
1
3
Order By: Relevance
“…The prevalence of nontraumatic meniscus lesions is 31% according to the Framingham study (9). Arthroscopic partial meniscectomy has been the first-line treatment for these injuries for a long time (3,4,(10)(11)(12) and positive clinical outcomes have been demonstrated for this procedure in several cohort studies (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of nontraumatic meniscus lesions is 31% according to the Framingham study (9). Arthroscopic partial meniscectomy has been the first-line treatment for these injuries for a long time (3,4,(10)(11)(12) and positive clinical outcomes have been demonstrated for this procedure in several cohort studies (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…Since previous non-randomized studies have demonstrated benefits for a surgical treatment of meniscus lesions (10)(11)(12), we put forward the hypothesis that there is a subgroup of patients that benefit from surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Langzeitstudien zeigen jedoch, dass bis zu 95 % der Patienten auch 10 Jahre nach partieller Meniskektomie zufrieden sind, sofern das Kniegelenk bandstabil ist und zum Zeitpunkt der Operation keine wesentliche Arthrose bestand [14]. Das Ausmaß der radiologischen Veränderungen nach arthroskopischer Meniskusoperation ist von der Größe des entfernten Meniskusanteils abhängig [3,28].…”
Section: Diagnostikunclassified
“…Alguns relatos demonstram piores resultados funcionais de meniscectomias no gênero feminino, com aumento da predisposição ao desenvolvimento de OA radiográfica do joelho (17,18,70,74) . Justificam tal ocorrência com argumentos anatômicos e epidemiológicos observados nas mulheres: valgismo mais acentuado do joelho, menor força muscular, maior incidência de frouxidão ligamentar e maior prevalência de OA de joelho (51) .…”
Section: Estatísticaunclassified